Simulating pathways of subsurface oil in the Faroe–Shetland Channel using an ocean general circulation model. Issue 1 (15th January 2017) - Main, C.E.; Yool, A.; Holliday, N.P.; Popova, E.E.; Jones, D.O.B.; Ruhl, H.A.
Abstract: Little is known about the fate of subsurface hydrocarbon plumes from deep-sea oil well blowouts and their effects on processes and communities. As deepwater drilling expands in the Faroe–Shetland Channel (FSC), oil well blowouts are a possibility, and the unusual ocean circulation of this region presents challenges to understanding possible subsurface oil pathways in the event of a spill. Here, an ocean general circulation model was used with a particle tracking algorithm to assess temporal variability of the oil-plume distribution from a deep-sea oil well blowout in the FSC. The drift of particles was first tracked for one year following release. Then, ambient model temperatures were used to simulate temperature-mediated biodegradation, truncating the trajectories of particles accordingly. Release depth of the modeled subsurface plumes affected both their direction of transport and distance travelled from their release location, and there was considerable interannual variability in transport. Highlights: Advective pathways in the model allowed detailed visualisation of the potential impact scenarios. Faroe–Shetland Channel circulation would strongly affect direction of transport depending on depth. Timing of an oil spill could have a critical effect on its severity. Deep waters of the FSC and Iceland basin could be more impacted than those further north. Pathways and transport extent are strongly determined by oil decay rate and subsurface plume depth.